2015
DOI: 10.1353/hpn.2015.0028
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Interaction and Use of Space in Traditional and Innovative Classrooms

Abstract: Despite myriad changes to language teaching methods over time, university-level classroom spaces have largely remained the same-until now. Recent innovations in classroom space design center on technological advances, include movable furniture and coffee-shop style rooms, and are believed to facilitate language learning in several ways. Specifically, compared to traditional classrooms, innovative spaces are designed in hopes of decreasing pre-task set-up, increasing student-centered interaction, and facilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
(19 reference statements)
1
13
0
Order By: Relevance
“…While learning is dependent upon the students' engagement in the learning process, student engagement is contingent upon the design of instruction; the physical space can improve student learning beyond the student's abilities measured by standardized tests; the design of learning spaces is thereby crucial (Brooks, 2011). Classrooms are believed to promote student-centered learning and to capitalize on student preferences and modern lifestyles (Gurzynski-Weiss et al, 2015). Truly innovative spaces will enhance learning opportunities in a variety of ways by decreasing pre-task setup, facilitating student-centered lessons, equalizing participation, and allowing students to work with more classmates than they would in traditional classrooms (Gurzynski-Weiss et al, 2015).…”
Section: Physical Space and Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…While learning is dependent upon the students' engagement in the learning process, student engagement is contingent upon the design of instruction; the physical space can improve student learning beyond the student's abilities measured by standardized tests; the design of learning spaces is thereby crucial (Brooks, 2011). Classrooms are believed to promote student-centered learning and to capitalize on student preferences and modern lifestyles (Gurzynski-Weiss et al, 2015). Truly innovative spaces will enhance learning opportunities in a variety of ways by decreasing pre-task setup, facilitating student-centered lessons, equalizing participation, and allowing students to work with more classmates than they would in traditional classrooms (Gurzynski-Weiss et al, 2015).…”
Section: Physical Space and Engagementmentioning
confidence: 99%
“…Classrooms are believed to promote student-centered learning and to capitalize on student preferences and modern lifestyles (Gurzynski-Weiss et al, 2015). Truly innovative spaces will enhance learning opportunities in a variety of ways by decreasing pre-task setup, facilitating student-centered lessons, equalizing participation, and allowing students to work with more classmates than they would in traditional classrooms (Gurzynski-Weiss et al, 2015). However, the reality is that unless teachers and instructors utilize a pedagogy that is functional with the intended use of the space, any design change based on learning will be irrelevant (Bouslama & Kalota, 2013;Dittoe, 2002).…”
Section: Physical Space and Engagementmentioning
confidence: 99%
“…Pattern coding is a way to "identify an emergent theme, configuration, or explanation" (Saldaña, 2009, p. 236) from the initial codes. This process of identifying descriptive codes and classifying them in broad themes was appropriate for gaining an initial encourage both students and instructors to move around in the room when engaged in collaborative tasks (Brooks, 2012;Gurzynski-Weiss et al, 2015), and social learning spaces can influence student engagement (Matthews et al, 2011). Continuing research on learning spaces can benefit from considering how physical space can facilitate the learning of both in-class students and telepresence robot users functioning as autonomous agents in the shared space.…”
Section: Discussionmentioning
confidence: 99%
“…However, both telepresence robot users and physically present students are affected by the physical space in the classroom. Research on the configuration of furniture in the classroom has shown that classrooms designed with group work in mind can encourage both students and instructors to move around in the room when engaged in collaborative tasks (Brooks, 2012; Gurzynski-Weiss et al, 2015), and social learning spaces can influence student engagement (Matthews et al, 2011). Continuing research on learning spaces can benefit from considering how physical space can facilitate the learning of both in-class students and telepresence robot users functioning as autonomous agents in the shared space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation